PLATE OSTEOSYNTHESIS FOR THE TREATMENT OF A COMPLEX METACARPAL FRACTURE IN A SAND GAZELLE (Gazella leptoceros) - MANSOUR, A.; BOUDEHENE, M. A.; BEGHOUL, S.; BOUSTEILA, A.; ABDELDJALIL, M. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A 5-month-old female gazelle (Gazella leptoceros) from Algeria was presented for consultation at the clinic, following a trauma that occurred when the gazelle was trapped in a wire mesh forelimb. The radiographic examination revealed a complex fracture displaced at the level of the left metacarpus, a surgical treatment by osteosynthesis was carried out, after approach and incision of the fracture site, a reduction and fixation of the bone was practiced using a screwed plate in steel and seven cortical bone screws, a suture by separate stitches was performed to close the skin, and a modified Robert Jones bondage was performed. X-rays performed 7, 15 and 21 days postoperative revealed very limited osteogenic activity and delayed healing despite bone alignment. This may be due to a defect in the periosteal vascularization linked to the direct surgical approach to the fracture.